Pemanfaatan Media Canva Dalam Pemeblajaran Fisika Untuk Meningkatkan Pengalaman Belajar Peserta Didik Di Kelas XI SMA Negeri 2 Kabupaten Pulau Morotai - Seba, Cut Sri Mainita; Malan, Irawati H (KUANTUM: Jurnal Pembelajaran dan Sains Fisika, 2024)
This research aims to determine how the use of Canva media in physics learning can enhance the learning experience of students in the 11th grade at SMA Negeri 2 Pulau Morotai and to assess the effectiveness of Canva media in improving the learning experience of students in the 11th grade at SMA Negeri 2 Pulau Morotai. The formulation of the research problem is as follows: (1) How is the utilization of Canva media in physics learning to enhance students' learning experiences, (2) How effective is the utilization of Canva media in physics learning to improve students' learning experiences in the XI grade at SMA Negeri 2 Kabupaten Pulau Morotai. The research method used in this study is the qualitative method. The subjects of this research are all students and a physics teacher in the 11th grade at SMA Negeri 2 Pulau Morotai. The research instruments used in this study include observation, interviews, questionnaires, and documentation. The data is then analyzed using percentage formulas and triangulation. From the research results, the observation of students showed 72.20% in the very good category, the observation of teachers showed 100% in the very good category, the teacher questionnaire showed 92.5% in the very feasible category, and the student questionnaire showed 67% in the very good/feasible category. Thus, it can be concluded that the use of the Canva application as an electronic-based learning media is very effective in enhancing the learning experience of students in the XI grade at SMA Negeri 2, Morotai Island Regency.